2011
DOI: 10.2169/internalmedicine.50.5834
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Diagnosis of Mediastinal and Hilar Lymph Node Metastases in Patients with Extrapulmonary Malignancy

Abstract: Objective The determination of mediastinal lymphadenopathy is important in the management of extrapulmonary malignancy. The purpose of this study was to determine the diagnostic performance of EBUS-TBNA in the diagnosis of mediastinal and hilar lymphadenopathy in patients with proven or suspicious extrapulmonary malignancy. Patients and MethodsRetrospective analysis was performed in 57 patients (81 lesions) with proven (n=51) or suspicious (n=6) extrapulmonary malignancies who underwent EBUS-TBNA between May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
4
28
1
Order By: Relevance
“…Additionally, NPV was 88.3% in this study, which was similar to the results of other studies that reported rates of between 76% and 86.9% (17,19,27,28). Five cases were diagnosed as malignancy after mediastinoscopy, although EBUS-TBNA results were reported as benign.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, NPV was 88.3% in this study, which was similar to the results of other studies that reported rates of between 76% and 86.9% (17,19,27,28). Five cases were diagnosed as malignancy after mediastinoscopy, although EBUS-TBNA results were reported as benign.…”
Section: Discussionsupporting
confidence: 89%
“…A large study of 161 suspected metastases from extrapulmonary malignancy patients undergoing EBUS-TBNA demonstrated a sensitivity rate of 87% (20). Other studies also showed a sensitivity rate of 85%-96.3% (15)(16)(17)(18) (Table 4). In the present study, the sensitivity of EBUS-TBNA in suspected metastases from extrapulmonary malignancy patients was 78.2%, which is lower than in other studies.…”
Section: Discussionmentioning
confidence: 98%
“…The diagnostic yield of EBUS-TBNA in patients with intrathoracic lymphadenopathy and a history of an extrathoracic malignancy is reported to be in the mid-80% [7,25,26]. In our cohort, 80% (20/25) of the patients with a final diagnosis of metastatic intrathoracic lymphadenopathy were diagnosed by EBUS-TBNA alone.…”
Section: Discussionmentioning
confidence: 69%
“…Song et al [27] showed that a definitive diagnosis for the evaluation of nodal metastases from an extrapulmonary malignancy was achieved by EBUS-TBNA in 61.4% (n=35) of 57 patients, allowing them to avoid surgery. Furthermore, Parmaksız et al [28] evaluated mediastinal and hilar lymph nodes in 48 patients with a history of an extrathoracic malignancy and demonstrated that EBUS-TBNA could be used to accurately diagnose mediastinal lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%